2023
DOI: 10.3390/antibiotics12010140
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Respiratory Microbiome in the Pathogenesis of Aspiration Pneumonia: Implications for Diagnosis and Potential Therapeutic Choices

Abstract: Although the lungs were considered to be sterile until recently, the advent of molecular biology techniques, such as polymerase chain reaction, 16 S rRNA sequencing and metagenomics has led to our expanding knowledge of the lung microbiome. These methods may be particularly useful for the identification of the causative agent(s) in cases of aspiration pneumonia, in which there is usually prior administration of antibiotics. The most common empirical treatment of aspiration pneumonia is the administration of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Probiotics (external microbes administered for health), prebiotics (nonabsorbed molecules that promote specific bacterial growth), antibiotics, and quorum-sensing molecule inhibitors are all examples of ways in which the microbiome of the lungs could be manipulated to correct dysbiosis and restore “healthy” microbial communities. It is considered that variations in the composition of the microbiota contribute to the vast spectrum of illness incidence and manifestation, which may provide an opportunity for therapeutic manipulation and precision medicine [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics (external microbes administered for health), prebiotics (nonabsorbed molecules that promote specific bacterial growth), antibiotics, and quorum-sensing molecule inhibitors are all examples of ways in which the microbiome of the lungs could be manipulated to correct dysbiosis and restore “healthy” microbial communities. It is considered that variations in the composition of the microbiota contribute to the vast spectrum of illness incidence and manifestation, which may provide an opportunity for therapeutic manipulation and precision medicine [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC is diagnosed in 85 percent of lung cancer cases ( Nyein et al., 2022 ; Xi et al., 2022 ). Bacterial lung infection (BLI) refers to a disease caused by microbial infection in the lungs, which induces inflammation and alters the lung microbiome environment ( Oliva and Terrier, 2021 ; Vallianou et al., 2023 ). In particular, BLI, as referred in this study, involves a variety of bacterial pathogens such as Streptococcus pneumoniae, Haemophilus influenzae, and Pseudomonas aeruginosa, all known for their capacity to colonize the respiratory tract and trigger infection.The World Health Organization’s 2021 Global Cancer Report indicated that 60% to 80% of NSCLC patients have concurrent BLI ( He et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…mNGS maps the acquired sequence information to the microbial resource database, overcoming the limitations of targeted detection methods, and characterizes all microorganisms in the human system through a single detection. The rapid development of mNGS has increased our understanding of the diversity, composition, and function of the lung microbiome (Miao et al, 2022;Xiao et al, 2022;Vallianou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%